PENGEMBANGAN MODEL INDUKTIF DALAM PEMBELAJARAN APRESIASI PUISI - Warsiman . (Fakultas Sastra Universitas Negeri Malang, 2011)
This research is conducted to improve the students‟ ability in appreciating poetry through the use of Inductive Model. This study applies Research and Development method which has been modified, and the result of the study is analyzed descriptively. The result of the study reveals that the use of Inductive Model is able to improve the students‟ ability in appreciating poetry by concerning eight instructional steps. The numerical improvement can be seen from the students‟ average scores in every treatment. On the first treatment, the students‟ average score is 60.9, the second treatment is 62.4 and on the third treatment is 65.3. Based on the criteria of success, the students‟ average scores seem to increase from the first treatment until the third treatment, from fair level into very good level. The first treatment shows an increase from fair level into excellent level. The second treatment shows an increase from good to very good. Finally, the third treatment shows an increase from very good to excellent level